Synodality of the Romanian Greek-Catholic Church (1964–2024): Evolution, Institutional Forms, and Identity Significance - Cristian Barta (Religions)
The Romanian Church United with Rome, Greek-Catholic, boasts a long and rich synodal tradition, with roots tracing back to the Metropolitanate of the Orthodox Romanians of Alba Iulia, which, at the close of the seventeenth century (1697–1700), re-established communion with the Church of Rome. The aim of the study I put forward is to analyse the evolution of synodality in the Greek-Catholic Church of Romania between the years 1964 and 2024, employing a methodology that will systematically relate historical, ecclesiological, and canonical aspects, thereby highlighting their identity implications. The structure of the article is determined by the principal stages through which the Greek-Catholic Church has traversed during the specified period: 1964–1989; 1989–2005; 2005–2024. These stages have witnessed profound transformations within the Greek-Catholic Church, including modifications to its canonical status that have also impacted its synodal life. In the year 1964, as the Second Vatican Council concluded and the decree Orientalium Ecclesiarum was approved, the Greek-Catholic Church of Romania was in the midst of severe communist persecution, having been outlawed since 1948. Its canonical status as a metropolitan province extra Patriarchatus was regulated by the Motu Proprio Cleri Sanctitati (2 June 1957), which recognised the institution of the provincial metropolitan synod, yet not that of the diocesan synod. Due to the persecution, the celebration of the metropolitan synod was not possible; however, privy conferences of bishops and diocesan ordinaries were held, which had significant effects on the life of the Church. The fall of communism, in December 1989, and the legalisation of the Greek-Catholic Church were followed by the publication, on 18 October 1990, of the Codex Canonum Ecclesiarum Orientalium. According to the new legislation, the Greek-Catholic Church regained the status of a Metropolitan Church sui iuris, a status unsuitable to its dignity and tradition since it lacked the institution of the synod. Indeed, the Council of Hierarchs, which under the presidency of the metropolitan archbishop governed the Church, did not constitute a synod but merely a form of exercising episcopal collegiality. Nevertheless, with the approval of the Holy See, the Fourth Provincial Council was held in Blaj (1997–2000). On 14 December 2005, Pope Benedict XVI elevated the Greek-Catholic Church of Romania to the dignity of a Major Archbishopric. Thus, the full attainment of synodality was achieved, with the supreme governing authority being the Major Archbishop and the Synod of Bishops. The proceedings of the Synod of Bishops of the Greek-Catholic Church have prompted institutional development, to be detailed in the article. This research will also illustrate the limitations of the current Codex Canonum Ecclesiarum Orientalium concerning the synodality of the Greek-Catholic Church.